ChirpArray: A low‐cost, easy‐to‐construct microphone array for long‐term ecoacoustic monitoring - Ryotaro Okamoto; Hiroyuki Oguma (Methods in Ecology and Evolution)
Abstract Advances in passive acoustic monitoring (PAM) have highlighted the importance of recording devices and audio recognition techniques in ecosystem monitoring. This study introduces ChirpArray, a cost‐effective and easily assembled microphone array for long‐term ecoacoustic monitoring of outdoor ecosystems. The ChirpArray system features a four‐channel microphone array that estimates sound source directions, aids in identifying individual animals and provides a detailed behavioural analysis. Unlike previous microphone arrays, ChirpArray is low‐cost, low‐power and waterproof, making it ideal for extended‐field monitoring. It is a fully open source and is constructed from readily available materials, ensuring broad accessibility for applications ranging from local citizen projects to large‐scale landscape recordings. This study details the power, storage consumption and localization performance of ChirpArray. Current measurements show that a small solar‐power set‐up can continuously operate the system. Localization tests using loudspeakers have yielded promising results. ChirpArray is a compact, energy‐efficient microphone array designed for long‐term outdoor recording, offering considerable advantages in ecoacoustic monitoring. Its exceptionally low power consumption allows for efficient and flexible deployment, making it an ideal solution for extended‐field monitoring and large‐scale landscape recordings.